Pengembangan Bahan Ajar Kosakata Dengan Media Kartu di MIN 1 Probolinggo - Wijaya, Mu’alim; Siti Maisuroh (Universitas Yudharta Pasuruan, 2022)
This research is development research that aims to describe how the process of developing vocabulary teaching materials using card media, measuring the validity and effectiveness of developing vocabulary teaching materials using card media. This research uses qualitative and quantitative research with the ADDIE model development approach. The respondents of this study were 24 students in third grade at Islamic junior high school (MIN) 1 Probolinggo. Data collection techniques using interviews, observation, documentation, questionnaires, and tests. The results of the research on the development of vocabulary teaching materials with this card media are by the needs of students where learning Arabic requires media to support learning. The results of the validation research on the development of vocabulary teaching materials with card media are based on an average of 94.62%, which means that this development book is very feasible to use. Based on the results of the pretest (before using the book) the test results showed 29.17% and the post-test results (after using the book) showed the results of 87.5%, meaning that the module for developing vocabulary teaching materials with card media was effective in learning Arabic at Islamic junior high school (MIN) 1 Probolinggo.